Evaluasi CIPP Terhadap Implementasi Skema Murur Dalam Ibadah Haji 1445 H - Fatikhaturrohmah, Salsabilla; Anasom, Anasom; Muhajarah, Kurnia; Rozaq, Abdul; Hilmi, Mustofa (Jayapangus Press, 2025)
The murur scheme is a preventive measure in organizing the Hajj in 2024 where this scheme is a form of evaluation of the implementation of the Hajj in the previous year which is intended to maintain the safety and comfort of the elderly, high risk, disabled, and their companions, especially in avoiding the density of Muzdalifah. This study aims to evaluate the implementation of the murur scheme using the CIPP (Context, Input, Process, Product) evaluation model. This research uses a qualitative approach with. Data were obtained through in-depth interviews and analyzed descriptively. The results show that the murur scheme is a policy of field challenges and has a positive impact on the level of congregation satisfaction, safety and efficiency of the Hajj pilgrimage, but still requires strengthening in the aspects of coordination, training of officers and provision of adequate facilities for more optimal implementation in the future. This research is expected to provide empirical and practical contributions to the development of Hajj service policies that are more adaptive, inclusive, and based on the needs of priority pilgrim groups in the future.